The Influence Of Marketing Mix And Quality Of Services On Interest In Intensive Patients' Revisits At PKU Muhammadiyah Hospital Yogyakarta City - Safrotul Laely; Hidayat, Muhammad Syamsu (International Journal of Healthcare Research, 2022)
Background : The research hospital experienced a decrease in inpatient visitors. During 2017-2020 the number of patient visits and BOR (Bed Occupancy Rate) decreased. The decrease in the number of patient visits will certainly have an impact on hospital admission costs, so hospitals must have the right strategy both in terms of marketing and service quality to continue to improve the brand and regain trust from the public. Method : In this research, the method used is quantitative with a cross sectional approach and purposive sampling technique. While the test used is the Chi Square test with a sample of 84 hospitalized patients. Results : The results of this study are the p-value in the marketing mix (0.079 > 0.05) with a correlation value of 0.193, which means that there is no significant effect between the marketing mix and the interest in repeat visits of inpatients with a very weak correlation value. While the p-value on service quality is (0.053 > 0.05) with a correlation value of 0.212, which means that there is no significant effect between service quality and interest in repeat visits with a weak correlation value. Conclusion : It can be concluded that there is no significant effect between the marketing mix and service quality on the interest in repeat visits of inpatients at PKU Muhammadiyah Hospital, Yogyakarta City.